(untitled) (Confluenţe Bibliologice, 2019)
Elena Ghica was the writer , who was able to make a European name, whose writings occupy an honorary place in all libraries in Europe, public or private”, said Cezar Bolliac, who, together with Radu Ionescu, drew attention the Romanian public on this brilliant writer. The works of Elena Ghica, with regret, are not known in the country because they have never translated into Romanian. In Russia her books have been translated since 1865-1866. Elena Ghica was appreciated for her literary work, but also for her soul qualities, over 30 biographers wrote about her life and and her work as a writer.